Imagem corporal de idosos institucionalizados - Machado, Aline dos Santos (2017)
Body image refers to a multidimensional construction that portrays how the individual perceives their body structure and physical appearance, being influenced by biological, social and cultural factors. Studies show that, in general, there is a dissatisfaction with body image among the elderly, but the aspects related to the perception of body image in this age group are still not well defined. Therefore, this study sought to analyze the body image of institutionalized elderly, identifying aspects that may intervene in this perception. The methodological procedures included a bibliographic review of the databases Biblioteca Virtual em Saúde (BVS), Scientific Electronic Library Online (Scielo), and United States National Library of Medicine (PubMed), including articles published between January 2007 and May 2017 that addressed the body image of the elderly and related factors. Later, the main results were analyzed, compiled and discussed. In addition, a descriptive and transversal study was carried out in three Long-Term Institutions for the Elderly (LTIE) of the municipality of Santa Maria, RS, Brazil, where the data of 38 elderly people were collected, according to the eligibility criteria, regarding body image (Stunkard's Figure Rating Scale), functional capacity (Katz Index), depression (Yesavage's Geriatric Depression Scale) and self-perception of health. With the results, two articles were elaborated. The first one is an integrative literature review, where it is possible to identify, through the analysis of the 17 selected articles, the relation between dissatisfaction with the image and excess body weight, female sex, negative health perception, more diseases and functional limitations. In the second article, by its turn, the results referring to the assessments in the ILPIs are presented, identifying a high prevalence of body dissatisfaction, while the functionality did not significantly interfere in this perception. On the other hand, a predictive symptomatology for depression and a self-perception of health exerted influence on the image. From this study, it is evident the importance of evaluating these variables in the elderly population and the need for multiprofessional interventions that promote healthy habits in the LTIEs in view of the corporal satisfaction.